Helicobacter pylori‐induced miR‐135b‐5p promotes cisplatin resistance in gastric cancer. Issue 1 (9th July 2018) - Shao, Linlin; Chen, Zheng; Soutto, Mohammed; Zhu, Shoumin; Lu, Heng; Romero-Gallo, Judith; Peek, Richard; Zhang, Shutian; El-Rifai, Wael
ABSTRACT: Helicobacter pylori infection is a major risk factor for the development of gastric cancer. Aberrant expression of microRNAs is strongly implicated in gastric tumorigenesis; however, their contribution in response to H. pylori infection has not been fully elucidated. In this study, we evaluated the expression of miR‐135b‐5p and its role in gastric cancer. We describe the overexpression of miR‐135b‐5p in human gastric cancer tissue samples compared with normal tissue samples. Furthermore, we found that miR‐135b‐5p is also up‐regulated in gastric tumors from the trefoil factor 1‐knockout mouse model. Infection with H. pylori induced the expression of miR‐135b‐5p in the in vitro and in vivo models. miR‐135b‐5p induction was mediated by NF‐κB. Treatment of gastric cancer cells with TNF‐α induced miR‐135b‐5p in a NF‐κB–dependent manner. Mechanistically, we found that miR‐135b‐5p targets Krüppel‐like factor 4 (KLF4) and binds to its 3′ UTR, leading to reduced KLF4 expression. Functionally, high levels of miR‐135b‐5p suppress apoptosis and induce cisplatin resistance. Our results uncovered a mechanistic link between H. pylori infection and miR‐135b‐5p‐KLF4, suggesting that targeting miR‐135b‐5p could be a potential therapeutic approach to circumvent resistance to cisplatin.—Shao, L., Chen, Z., Soutto, M., Zhu, S., Lu, H., Romero‐Gallo, J., Peek, R., Zhang, S., El‐Rifai, W. Helicobacter pylori‐induced miR‐135b‐5p promotes cisplatin resistance in gastric cancer. FASEB J. 33, 264–274 (2019). www.fasebj.org